Legal, Social and Health Literacy Improvement Program for Adolescents through Community Education - M. Rusdi; Ismail Ismail; La Isini; Siti Syahsyidatul Ulfa; Abdul Raihan (PT. Global Research Collaboration, 2025)
This community engagement program aims to enhance adolescents’ literacy in legal, social, and health aspects through a participatory community-based education approach. The main partner of this program is the Ambon City Child Forum, which serves as an advocacy platform for youth involvement in local child-friendly city initiatives. The program was implemented in July 2025 in Ambon City, involving 30 adolescent participants who are active members of the forum. The implementation utilized interactive learning methods including participatory lectures, group discussions, case simulations, and role plays designed to address issues related to legal protection, social interaction, and reproductive health among adolescents.The results demonstrate a significant improvement in both knowledge and attitudes among participants. The average score increased from 52.3 (pre-test) to 85.7 (post-test), indicating a 33.4-point improvement after the intervention. Furthermore, 70% of participants reported greater confidence in reporting cases of violence, while 75% became more open to discussing reproductive health issues. The program also established the Child Forum Literacy Working Group, which focuses on continuing peer education activities in schools and surrounding communities. This initiative not only improved adolescents’ multidimensional literacy but also strengthened the role of the Ambon City Child Forum as a peer education and advocacy agent at the local level. Moreover, the program contributes directly to the achievement of several Sustainable Development Goals (SDGs )notably Goals 3, 4, 5, and 16 by fostering a generation of youth who are legally aware, socially empathetic, and physically as well as mentally healthy.